REAKTUALISASI PEMIKIRAN IBN QAYYIM AL-JAUZIYYAH DALAM PENGEMBANGAN TASAWUF - Arikhah, Arikhah (At-Taqaddum, 2016)
Sufism is considered as the cause of the destruction and bankruptcy of civilization. The presumption is based on the allegation that Sufism teaches thoughts of pantheism (doctrine that equates God with the forces and laws of the universe), cult (worship) on the human individual (including the trustee), drunkenness and insanity (ekstatisme/sya????t), the story of suprarasional abilities, experiences that do not make sense and heresy, as well as other misguided thinking.In the thought of Sufism, Ibn Qayyim called ijtihad implementation of Sufism by referring back to the al-Quran and al-Hadith, prioritize science than Sunnah worship, perform ijtihad that Sufism is not blind following to the masy?yikh, do contextualization of Sufism appropriate time and place (Zaman wa eat) so understood Muslims all the time, do not isolate themselves from social life and make a series of Salik on the way to God (sair ilallah) not required sequence (tartib Gair musta?iqq), but optional (musta?san).Ibn Qayyim see Islam builds the concept of life departed from the faith, Islam and charity. Ibn Qayyim thinking about the meaning of the ascetic, more encouraging as the efforts for the improvement of human life, instill a positive attitude to the world and dare to face the reality of life and the challenges of advancement of age. In solitude, Ibn Qayyim requires a deep appreciation of esoteric religious but did not retreat from social life, but still actively involved in the community. The principles of balance (tawazun) are the laws for the entire universe. Therefore, Ibn Qayyim considers that violate the principle of balance is a cosmic sin, for breaking the law of Allah which controls the universe. Through remembrance, Ibn Qayyim explained that dhikr in complete sentences and meaningful then one more assured in terms of their faith because of a similar phrase that is active, confirmed the meaning and certain attitudes are positive and good. In trust, Ibn Qayyim said closely related to the plans and efforts. If the plan is ripe, the results were submitted to Allah SWT.